![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
展开全部
解(1):tan(α-β)
=(tanα-tanβ)/(1+tanαtanβ)
=(2+1/3)/(1-2×1/3)
=(7/3)/(1/3)
=7
(2):tan(α+β)
=(tanα+tanβ)/(1-tanαtanβ)
=(2-1/3)/(1+2×1/3)
=(5/3)/(5/3)
=1
因为0<α<π/2,π/2<β<π
所以0+π/2<α+β<π/2+π
π/2<α+β<3π/2
所以tan(α+β)=tan(5π/4)=1
α+β=5π/4
=(tanα-tanβ)/(1+tanαtanβ)
=(2+1/3)/(1-2×1/3)
=(7/3)/(1/3)
=7
(2):tan(α+β)
=(tanα+tanβ)/(1-tanαtanβ)
=(2-1/3)/(1+2×1/3)
=(5/3)/(5/3)
=1
因为0<α<π/2,π/2<β<π
所以0+π/2<α+β<π/2+π
π/2<α+β<3π/2
所以tan(α+β)=tan(5π/4)=1
α+β=5π/4
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询